Optimization of Students' Learning Outcomes in Information and Communication Technology through Visual Media in Grade VII of Junior High School - Yunulius, Yunulius (Jurnal Pendidikan Vokasi Indonesia, 2024)
Image-based learning media is a tool that teachers can use in the teaching process with the aim of creating meaningful learning experiences for students. Thus, the role of a teacher, who possesses expertise, determination, and the ability to use such media, significantly influences the development of students' interest in learning. This study aims to describe the use of image media in enhancing the learning interest of seventh-grade students at SMP MTs Al-Hidayah. This research is a qualitative study, where the researcher describes the use of image media to improve the learning interest of seventh-grade students at SMP MTs Al-Hidayah through in-depth interviews, supported by observations and documentation. The research subjects included the school principal, the seventh-grade teacher, three subject teachers, and all seventh-grade students, totaling 21 participants. The data analysis technique used was flow analysis, including data reduction, data presentation, and verification stages. The findings indicate that the teacher's strategy in utilizing image media to enhance student interest in learning at SMP MTs Al-Hidayah includes: adjusting the material to the images used considering media limitations, organizing steps in using image media, and aligning learning steps based on the lesson plan (RPP), references, and the previously established learning objectives.